Modified pressure-cooker technique (PCT) using extra-soft Kaneka coils improves embolization of high-grade cerebral arteriovenous malformations: a technical note - Mahmut Yüksel; Marios Psychogios; Kristine Blackham (Egyptian Journal of Neurosurgery, 2023)
Abstract Endovascular embolization techniques are showing an extraordinary potential to treat patients suffering from complex neurovascular malformations. The embolization with liquid embolic agents via Onyx is a prominent approach to treat arteriovenous malformation (AVM). However, intraoperative reflux of the liquid agents can be very challenging and, thus, is impairing full success of endovascular treatment. A possible technique to prevent intraoperative endovascular reflux is the pressure-cooker technique (PCT) utilizing coils to build a wedge proximal to the AVM. Few modifications of the PCT have been developed in the recent years to improve effectiveness of embolization procedure. Hereby, we present a novel PCT modification utilizing extra-soft Kaneka coils and glue to build well-fitting wedges. After the application of extremely soft bare coils with high trackability, flexibility and crossability, liquid agents can be injected with reduced reflux. We think the pressure-cooker technique with extra-soft Kaneka coils enables more efficient embolization in even farther, tinier and more tortuous target vessels. This technical note presents two illustrative patient cases with treatment-refractory, high-grade cerebral arteriovenous malformations which were successfully treated via embolization with PCT in which the plug was formed with Kaneka coils.